2008
DOI: 10.1016/j.jpubeco.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Political polarization and the electoral effects of media bias

Abstract: Many political commentators diagnose an increasing polarization of the U.S. electorate into two opposing camps. However, in standard spatial voting models, changes in the political preference distribution are irrelevant as long as the position of the median voter does not change. We show that media bias provides a mechanism through which political polarization can affect electoral outcomes.In our model, media firms' profits depend on their audience rating. Maximizing profits may involve catering to a partisan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(188 citation statements)
references
References 15 publications
3
179
2
4
Order By: Relevance
“…For example, media probably plays a role in shaping political preferences. Bernhardt et al (2008) develop a model that predicts that profit-maximizing media firms may have an incentive to supply biased news to partisan audiences, and DellaVigna and Kaplan (2007) and Gerber et al (2006) have empirically shown that biased media actually affects voting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, media probably plays a role in shaping political preferences. Bernhardt et al (2008) develop a model that predicts that profit-maximizing media firms may have an incentive to supply biased news to partisan audiences, and DellaVigna and Kaplan (2007) and Gerber et al (2006) have empirically shown that biased media actually affects voting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This question is increasingly relevant firstly due to the development of social media. In recent sociological literature the issue of increasing polarization due to the development of social media and the Internet in general (see, e.g., [28,29]), and the impact of polarization on political events [30] is widely discussed.…”
Section: № 1 / 2017 67mentioning
confidence: 99%
“…However, in this case we might face a principal agent problem between shareholders and managers. Baron (2006) and Bernhardt et al (2008) argue that the trade-off between economic and social or political goals is not automatically given. Instead media bias could even be a profit maximizing 47 strategy.…”
Section: Competition Effects On the Diversity Of Opinion In Media Marmentioning
confidence: 99%